Prevalence of Multidrug-Resistant Organisms in Hospital Samples: A Microbiology Lab Survey - Almutairi, Fawaz Atqan; Alghamdi, Faisal Saleh; Almutairi, Osama Munif; Alotaibi, Nader Faihan; Al-Mutairi, Ahmed Faisal; Linjawi, Emtenan Hassan (Journal of Neonatal Surgery, 2026)
Background: Due to the significant clinical impact, the continuously growing amount of multidrug-resistant organisms (MDROs) continues to be problematic in hospital environments. The goal of this study is to understand the amount and contributing factors of MDROs found in clinical samples collected in hospitals. Method: A total of five hundred clinical samples, collected from patients in all hospital divisions, were used. The antibiotic susceptibility patterns of the bacterial isolates were determined using standard microbiological methods. Multidrug resistance was quantified as resistance to at least one antimicrobial agent from three or more classes of the myriad of available antmicrobials. Using statistical methods, the relationship between the factors of interest and MDR was analyzed. Results: Of the 470 samples yielding microbiological growth, 240 (51%) samples contained MDR organisms. The three most frequently isolated organisms were Escherichia coli (42%), Klebsiella pneumoniae (25%), and MRSA (12%). MDR infections were associated with previous antibiotic use (75%) and prolonged hospital stays (more than 7 days) (p < 0.05). The greatest frequency of MDR organisms was isolated from the ICU (42%). Conclusion: The results of this study confirm that there is a high frequency of MDRO organisms in hospitals. The study confirms the relationship of previous antimicrobial use, prolonged hospital stays, and the frequency of MDR organisms in hospitals. To help combat this growing healthcare concern, hospitals need to employ more strict infection control measures, implement better antimicrobial stewardship policies, and do more active surveillance to monitor and control the potential outbreak of resistant organisms